Hormonal Regulation of Ovule Initiation in Arabidopsis - Daniela Barro-Trastoy; Maria Dolores Gomez; Pablo Tornero; Miguel A. Perez-Amador (Journal of Plant Growth Regulation, 2024)
As seed precursors, ovules are fundamental organs during the plant life cycle. Decades of morphological and molecular study have allowed for the elucidation of the complex and intricate genetic network regulating ovule development. Ovule and seed number is highly dependent on the number of ovule primordia that are determined from the placenta during early pistil development. Ovule initiation is positively regulated by the plant hormones auxins, cytokinins, and brassinosteroids, as well as negatively regulated by gibberellins. Each hormone does not act independently; multiple points of hormonal crosstalk occur to coordinately regulate ovule primordia initiation. In this review, we highlight the roles of these hormones and their interactions in the genetic and hormonal network co-regulating ovule initiation in Arabidopsis.